The Influence of Good Corporate Governance and Disclosure Corporate Social Responsibility towards Mining Sector Company Value - Haisyah, Nurul; Hendarmin, Rum; Pebriani, Reny Aziatul (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to determine and explain the effect of GCG and CSR on firm value. The population of this study was all mining companies listed on the Indonesia Stock Exchange for the 2016-2019 period as many as 47 companies. The sample in this study was 16 companies. The sampling technique was purposive sampling. The data analysis technique in this research was Partial Least Square (PLS). The results show that (1) Good Corporate Governance (GCG) has an insignificant and negative effect on firm value, (2) Corporate Social Responsibility (CSR) has a significant effect but negative coefficient on firm value, (3) Good Corporate Governance ( GCG) and Corporate Social Responsibility (CSR) simultaneously have a significant and positive effect on firm value.